Association between obesity, common chronic diseases and health promoting lifestyle profiles in Hong Kong adults: a cross-sectional study - Yan Sin Leung; Jack Jock Wai Lee; Maria Ming Po Lai; Chole Kei Ming Kwok; Ka Chun Chong (BMC, 2020)
Abstract Background Recent surveys revealed that the health status of many people from Hong Kong is far from ideal. Although non-communicable diseases are largely preventable, few relevant health promotion and disease prevention programs are available. Thus, we assessed the health indicators of Chinese adults in Hong Kong to investigate the relationship between obesity, common chronic diseases, and health-promoting lifestyle profiles to provide inspirations for decision makers in formulating targeted disease prevention and health management programs. Methods This is a secondary analysis of a data set of 270 community-dwelling Hong Kong adults who were within the eligible age range between 18 and 80 years without eye diseases that affect retinal photographs. The study exposure variable, health-promoting lifestyle profiles, was measured using the Health-Promoting Lifestyle Profile II (HPLP-II) questionnaire. The primary outcome variable, obesity, was defined using body mass index and waist-hip ratio. The secondary study outcome, estimated chronic diseases, including of anemia, chronic kidney disease, and cardiovascular disease, were estimated using automatic retinal image analysis from the retinal images. Data were analyzed using tests of proportion, the independent sample t-tests, Welch's t-test, and binary logistic regression models. Results All HPLP-II subscales had positive responses (≥ 2.5). Significant differences were noted between men and women in the health responsibility and nutrition subscales (Health Responsibility: p = 0.059; Nutrition: p = 0.067). Regression models revealed that nutrition (adjusted odds ratio [AOR] = 0.41; p = 0.017), physical activity (AOR = 0.50; p = 0.015), interpersonal relations (AOR = 2.14; p = 0.016), and stress management (AOR = 2.07; p 0.038) were associated with obesity; while spiritual growth (AOR = 0.24; p = 0.077) and interpersonal relations (AOR = 5.06; p 0.069) were associated with estimated chronic kidney disease. Conclusions Improving health behaviors may control or alleviate the prevalence of obesity and chronic kidney disease. These findings could arouse concern about lifestyle behaviors and promote self-assessment of health-promoting lifestyles to the general public. The study also provided new insights into the relationship between the HPLP-II and other common chronic diseases that warrant further study.